Dilute Magnetic Semiconductor Cu2FeSnS4 Nanocrystals with a Novel Zincblende Structure. (9th June 2012) - Liang, Xiaolu; Wei, Xianhua; Pan, Daocheng
Abstract : Diluted magnetic semiconductor Cu 2 FeSnS 4 nanocrystals with a novel zincblende structure have been successfully synthesized by a hot-injection approach. Cu +, Fe 2+, and Sn 4+ ions occupy the same position in the zincblende unit cell, and their occupancy possibilities are 1/2, 1/4, and 1/4, respectively. The nanocrystals were characterized by means of X-ray diffraction (XRD), transmission electron microscopy (TEM), selected area electron diffraction (SAED), energy-dispersive spectroscopy (EDS), and UV-vis-NIR absorption spectroscopy. The nanocrystals have an average size of 7.5 nm and a band gap of 1.1 eV and show a weak ferromagnetic behavior at low temperature.